العنف الأسري ودوره في تنمية ميول الارهاب نحو الابناء - الأسمر عبير مصطفى (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
The subject of the research deals with a serious problem, which is the phenomenon of domestic violence, which plays a major role in the development of terrorist tendencies, especially among children. The aim of the research was to uncover domestic violence and its relationship to some psychosocial problems in children (childhood), and the importance of this research appears in identifying a few Theoretical approaches, and the researcher’s attempt to benefit from the theoretical heritage in (almost) everything written about domestic violence. The researcher concluded, with the descriptive approach, that there are many factors that lead to the phenomenon of violence against children, the most important of which are: - Social upbringing based on tolerance, friendliness and national fusion inside and outside the family. A clear correlation between domestic violence and children’s abnormal behavior. The emergence of physical violence, both physical and moral, and their resulting negative effects on the personality of children.